Revitalisasi Tempat Pembuangan Akhir(TPA) Menjadi Objek Wisata Edukasi Sebagai Upaya Meningkatkan Taraf Ekonomi Masyarakat: Studi Kasus di TPA Pakusari, Kabupaten Jember - Hasbi Ash Shiddiqi; Wildan Miftahussurur; M. Rofiullah Ash-Shudiq; M.Ikomuddin; Adjie Tara Syaputra; Moch Azhaim Ibrahim; M. Zainul Fata; Moh. Jakfar Assodiq; M. Musleh; Mahfid Baitullah; Muhammad Latif (Pusat Riset dan Inovasi Nasional, 2023)
Waste is a very important problem of concern today. The amount of waste is increasing day by day, causing harm to health and the environment. For this reason, managing a waste landfill into a tourist attraction with an educational nuance is very interesting to research. This research wants to describe whether this tourist attraction can provide benefits to the surrounding community, for example as a place to earn a living such as selling food or drinks around the landfill. Visitors are very happy and really agree with the existence of this tourist attraction. Because, this tourist attraction has benefits for visitors who come, for example visitors can learn how to process waste by making recycled waste and fertilizer from waste. Visitors also enjoy coming to this tourist spot because the place is beautiful and comfortable to use to relax and relieve fatigue after work. Educational tourism objects are also presented, such as how to process waste, make fertilizer from waste materials (compost), learn about methane gas and look closely at how to learn how to recycle waste materials. TPA can be a place for education/learning about how to process waste, differentiate between organic and inorganic waste, make compost, make crafts from recycled waste.